Impact of epicardial adipose tissue volume quantified by non-contrast electrocardiogram-gated computed tomography on ergonovine-induced epicardial coronary artery spasm. (15th October 2016) - Ito, Tsuyoshi; Fujita, Hiroshi; Ichihashi, Taku; Ohte, Nobuyuki
Abstract: Objective: Endothelial dysfunction of the coronary artery is thought to lead to the development of coronary spasms. Epicardial adipose tissue may be a marker of coronary atherosclerosis. This study investigated the diagnostic impact of epicardial fat volume (EFV), quantified with non-contrast electrocardiogram (ECG)-gated computed tomography (CT), on ergonovine-induced coronary spasms. Methods: We included 97 patients with suspected coronary spastic angina who underwent ECG-gated CT and an ergonovine provocation test. The EFV was measured with CT data sets using dedicated software. Coronary spasm was defined as total or subtotal occlusion (compared with the relaxed state after nitroglycerin) that was associated with ischemic ECG changes and concurrent chest pain. Results: Coronary spasms were observed in 27 patients (28%). The EFV was significantly higher in patients with spasms compared with those without spasms (175.0 ± 57.8 cm 3 vs. 129.7 ± 57.8 cm 3, p < 0.01). Univariate logistic regression analyses indicated significant relationships between coronary spasms and EFV (per 10 cm 3, odds ratio (OR): 1.13; p < 0.01), male gender (OR: 3.34; p < 0.01), and smoking (OR: 3.42; p < 0.01). In the multivariate model, EFV (per 10 cm 3, OR: 1.10; p = 0.03) and male gender (OR: 5.94; p = 0.02) remained significant predictors of coronary spasm. The optimal EFV threshold for predicting coronary spasm was 149.4 cm 3, identified with a receiver operating characteristic curve. Conclusions: Increased EFV was associated with ergonovine-induced epicardial coronary artery spasms.